2018
DOI: 10.1073/pnas.1710323115
|View full text |Cite
|
Sign up to set email alerts
|

Laminar recordings in frontal cortex suggest distinct layers for maintenance and control of working memory

Abstract: SignificanceThe anatomy and dynamics of different layers of the cerebral cortex are distinct. Physiological work in the sensory cortex has investigated how different layers process sensory inputs, and how they are engaged during attention tasks. In the frontal and prefrontal cortices, where lamination is present, very few studies have investigated the role of distinct layers for cognition. We studied frontal cortex laminar neuronal activity as monkeys performed working memory tasks. Spiking and gamma-band acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

37
252
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 259 publications
(309 citation statements)
references
References 37 publications
37
252
1
Order By: Relevance
“…It has been suggested that the key function of gamma synchrony is to regulate communication between groups of neurons in order to dynamically reconfigure circuits and generate diverse forms of behavior 7,9,12,13,30 . However, the functional significance of synchronization across neuronal structures, particularly at gamma-frequencies, has long remained one of the most controversial topics in systems neuroscience 31,11,32,18,33,7,8 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that the key function of gamma synchrony is to regulate communication between groups of neurons in order to dynamically reconfigure circuits and generate diverse forms of behavior 7,9,12,13,30 . However, the functional significance of synchronization across neuronal structures, particularly at gamma-frequencies, has long remained one of the most controversial topics in systems neuroscience 31,11,32,18,33,7,8 .…”
Section: Discussionmentioning
confidence: 99%
“…Dynamic processes within the prefrontal cortex that facilitate this kind of behavioral adaptation remain unknown. Synchrony, particularly in the gamma-frequency range (~30-80 Hz), has been proposed to regulate how neurons interact with each other and their downstream targets [3][4][5][6][7][8][9][10][11][12][13] . Thus, by selectively enhancing interactions between neurons in specific brain regions at particular moments, synchrony could generate dynamic brain states to support behavioral adaptation.…”
Section: Introductionmentioning
confidence: 99%
“…These considerations might help to understand why those two sensorimotor rhythms are often aggregated into the same (mu-) rhythm category (Cuevas et al, 2014;Hari, 2006). Having shown that those two rhythms are anatomically and functionally distinct phenomena, it becomes relevant to know whether alpha and beta rhythms can also be systematically differentiated in other frontal brain regions (Bastos et al, 2018;Johnston et al, 2019).…”
Section: Interpretational Issuesmentioning
confidence: 99%
“…Yet, the neurophysiological characteristics of alpha-and beta-band rhythms have often been studied by aggregating these two rhythms into the same (mu-) rhythm category (Cuevas et al, 2014;Hari, 2006;Miller et al, 2010), an approach often justified by the partial overlap in their spatial and spectral distributions (Bressler and Richter, 2015;Haegens et al, 2014;Salmelin and Hari, 1994;Szurhaj et al, 2003) and by the temporal correlation of their power envelopes (Carlqvist et al, 2005;de Lange et al, 2008;Tiihonen et al, 1989). By aggregating those rhythms, it has been recently shown that 4-22 Hz activity modulates high-frequency broadband power in primates' frontal cortex (Bastos et al, 2018;Johnston et al, 2019), and that 10-40 Hz activity is spatially organized in traveling waves (Takahashi et al, 2015). It remains unclear, however, whether that aggregation could obscure differential contributions of those rhythms to movement selection.…”
Section: Introductionmentioning
confidence: 99%
“…These types of short-lived prediction effects might seem surprising if one assumes that pre-activated mental representations are necessarily accompanied by sustained detectable neural activity. However, evidence from intracranial recordings of local neural activity (Mongillo et al, 2008;Stokes et al, 2013;Lundqvist et al, 2016;Bastos et al, 2018;Lundqvist et al, 2018b), and from noninvasive EEG and fMRI recordings of global brain activity (Sprague et al, 2016;Wolff et al, 2017), suggests that, instead of being persistent, neural activity over delays can be relatively sparse, especially when other information is concurrently activated from long term memory (Kaminski et al, 2017). During these delays, anticipated information remains accessible, but it can only be detected when perturbed or "pinged", e.g.…”
Section: The Time Course Of the Prediction Effectmentioning
confidence: 99%